Treatment of refractory acute gout by invigorating spleen, raising Yang, dehumidifying, and dredging collaterals: A metabolomics study - Liang Weidong; Chen Liuting; Lin Haiyang; Peng Jianhong; Ye Xueying (Elsevier, 2022)
Objective: This study aimed to use proton nuclear magnetic resonance technology to analyze the metabolic pathways of invigorating the spleen and promoting Yang dehumidification and dredging collaterals (Cassia twig Peony Anemarrhenae and Rise Yang Dehumidification Decoction) in treating the acute attack of refractory gout and to find the target of traditional Chinese medicine (TCM). Method: Forty patients with acute refractory gout of spleen deficiency and dampness-heat type were recruited and randomly divided into TCM group and the Western medicine group, with 20 patients in each group. Serum samples were collected before and after 10 days of treatment for comparative analysis, and the metabolic pathways were identified. Combined with the results of TCM syndrome score, inflammatory indexes (C reactive protein, erythrocyte sedimentation rate), and creatinine, adiponectin, and cytokine (interleukin-6, tumor necrosis factor-α) levels before and after treatment, the mechanism of TCM action was analyzed. Results: Cassia twig Peony Anemarrhenae and Rise Yang Dehumidification Decoction were found to be better than Western medicine in alleviating joint swelling and pain, localized as well as systemic fever, and bitter and dry mouth. Furthermore, inflammatory indicators, cytokines, creatinine, and adiponectin levels were better in the TCM group than in the Western medicine group. In terms of metabolic pathways, the treatment of an acute attack of refractory gout with our TCM compounds resulted in better improvements in branched-chain amino acid (BCAA) metabolism, glycine, serine, and threonine metabolism, tyrosine metabolism, taurine, and low taurine metabolism, glycolysis/sugar dysplasia, synthesis and degradation of ketone body, D-glutamine metabolism, citric acid cycle (TCA cycle), glyceride metabolic pathways, etc., than the use of Western medicine. Conclusion: TCM compounds may improve the metabolic network of refractory acute gout by stimulating the above metabolic pathways to inhibit the inflammatory response, relieve joint pain, and augment glucose metabolism, energy metabolism, and lipid metabolism. These compounds are hence worthy of promotion.